Eficacia del tratamiento sintomático de rinitis en el Hospital General Isidro Ayora - Ordóñez Ávila, Jonathan Eduardo (2019)
Rhinitis is a heterogeneous disorder that occurs with inflammation of the nasal mucosa, presenting a clinical picture of obstruction, sneezing, rhinorrhea and nasal pruritus. In order to carry out the current research, the following objectives were set: to determine the main symptoms in patients with rhinitis, to classify the symptoms of rhinitis according to the sub-scales of the SNOT-20 survey and to evaluate symptoms after symptomatic treatment with nasal washes using hypertonic saline solution in patients with diagnosis of rhinitis in the “Isidro Ayora” general hospital, being a prospective, quantitative cross-sectional study. In which 50 patients who attended an outpatient clinic participated; to who was applied a before and after symptomatic treatment, the SNOT-20 scale, which is an instrument that allows recording the intensity of rhinitis symptoms and their impact on the quality of life; Nasal washes were performed for 30 consecutive days, the results showed that the main symptoms are the need to blow your nose, frequent sneezing, thick nasal secretion and falling secretion back to the throat with an incidence of 100% (n = 50). Rhinological and sleep symptoms are the most frequent in rhinitis, presenting an incidence of 93.3% (n = 280 points) and 77.7% (n = 233 points) respectively. The incidence of all post treatment symptoms decreased; The need to blow your nose and having frequent sneezing were the symptoms that showed the greatest reduction with 86% (n = 43) and 78% (n = 39) respectively. Concluding that nasal washes with hypertonic saline solution are effective in improving the quality of life of patients with rhinitis. Keywords: Nasal washes, hypertonic solution, Sino- Nasal Outcome Test - 20